2016
DOI: 10.1016/j.jid.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of Intact Hair Follicles and Pilosebaceous Units by Volumetric Multispectral Optoacoustic Tomography

Abstract: Visualizing anatomical and functional features of hair follicle development in their unperturbed environment is key in understanding complex mechanisms of hair pathophysiology and in discovery of novel therapies. Of particular interest is in vivo visualization of the intact pilosebaceous unit, vascularization of the hair bulb, and evaluation of the hair cycle, particularly in humans. Furthermore, noninvasive visualization of the sebaceous glands could offer crucial insight into the pathophysiology of follicle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…Optoacoustics offers the unique capacity for high resolution 3D optical mapping of tissue by further delivering highly specific optical contrast from a depth of several millimetres to centimetres in living tissues. A recent study performed on human volunteers, has shown capacity for non-invasive structural and functional analysis of intact hair follicles and pilosebaceous units by volumetric handheld MSOT [339]. On-the-fly assessment of key morphometric parameters of follicles and lipid content as well as functional oxygenation parameters of the associated capillary bed was demonstrated with high spatial resolution below 70μm.…”
Section: Applications Enabled By Optoacoustic Visualization Of Multmentioning
confidence: 99%
“…Optoacoustics offers the unique capacity for high resolution 3D optical mapping of tissue by further delivering highly specific optical contrast from a depth of several millimetres to centimetres in living tissues. A recent study performed on human volunteers, has shown capacity for non-invasive structural and functional analysis of intact hair follicles and pilosebaceous units by volumetric handheld MSOT [339]. On-the-fly assessment of key morphometric parameters of follicles and lipid content as well as functional oxygenation parameters of the associated capillary bed was demonstrated with high spatial resolution below 70μm.…”
Section: Applications Enabled By Optoacoustic Visualization Of Multmentioning
confidence: 99%
“…To the best of our knowledge, microscopic optoacoustic devices have not yet entered clinical research . Optoacoustic mesoscopy methods use non‐focused illumination schemes in combination with a focused ultrasound detector, which enables imaging to depths of several millimetres while keeping high resolution . A fundamental limitation of previous systems has, however, been the narrow bandwidth of the applied ultrasound detectors.…”
Section: Dermatologic Imaging Using Raster‐scan Optoacoustic Mesoscopymentioning
confidence: 99%
“…Given the wide disparity in the experimental settings evaluating the efficacy and safety of antiseptics as well as the conflicting results observed over the years, the AWG believes that new standardized and clinically relevant studies, using in vitro and in vivo models, along with novel noninvasive measurement systems, to compare antimicrobial efficacy and toxicology are the need of the day. Some tools to study in vitro and in vivo absorption and distribution of various compounds in wounds, which are currently being investigated, include in vitro skin-on-achip microfluidics and in vivo Raman spectroscopy and photoacoustics [74] . The differences in the study parameters under evaluation -assessment times, antiseptic concentrations and formulations, and the wound modelsimpact the results of the studies and should be carefully considered when arriving at conclusions.…”
Section: Pvp-i In Wound Care Management In Asiamentioning
confidence: 99%